Facile synthesis of SnS2@g-C3N4 composites as high performance anodes for lithium ion batteries - Ha Tran Huu; Hang T.T. Le; Thanh Huong Nguyen; Lan Nguyen Thi; Vien Vo; Won Bin Im (My University, 2021)
Facile synthesis of SnS2@g-C3N4 composites as high performance anodes for lithium ion batteries
Keywords: Anode Pin Li-ion; SnS2@g-C3N4; Hiệu suất tích trữ